Sex Determinasi pada Manusia dan Karakteristik Sex yang Terikat - Anjani, Arum Dwi; Aulia, Devy Lestari Nurul (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
In this study, the purpose of this study was to deepen information about sex determination, especially sex determination in humans. The research method used is the literature review method by utilizing several sources, both national and international journals related to relevant research results on "Sex determination". The results of the study showed that the sex determination system in humans depends entirely on the combination of sex chromosomes, without the influence of environmental or epigenetic factors.